2014
DOI: 10.1021/bm5011799
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cellulose Nanofibril Bound Silver Nanoprism for Surface Enhanced Raman Scattering

Abstract: Silver nanoprisms (AgNPs) were robustly synthesized using TEMPO-oxidized cellulose nanofibrils (CNFs) as a dual capping and shape-regulating agent for the first time. Reducing AgNO 3 with NaBH 4 in CNF suspensions produced smaller but more uniform Ag nanospheres (AgNSs) with increasing Ag + /CNF ratios. CNF bound AgNSs were facilely transformed to AgNPs by etching with H 2 O 2 , supporting the capping and shape-regulating capability of CNFs. AgNPs could also be synthesized directly in a one-shot reduction reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…Only a few attempts have been made on the bioassisted seeded growth of shape-selective noble NPs with improved morphological yield. 46,47 Previously, our group has demonstrated that the morphology and optical properties of noble metal NPs could be modulated by the concentration and the structure of the CTPR proteins. 48 CTPR is a de novo protein sequence based on the tertratricopeptide repeat family.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few attempts have been made on the bioassisted seeded growth of shape-selective noble NPs with improved morphological yield. 46,47 Previously, our group has demonstrated that the morphology and optical properties of noble metal NPs could be modulated by the concentration and the structure of the CTPR proteins. 48 CTPR is a de novo protein sequence based on the tertratricopeptide repeat family.…”
Section: Introductionmentioning
confidence: 99%
“…18 Serving as a¯rst reported stabilizer, citrate has been widely used because its three-fold symmetry can preferentially match Ag (111) facets, blocking the growth along the vertical axis and allowing extensive growth along the lateral direction. [19][20][21] Except for citrate capping, hydroxyl group-containing molecules, such as ethanol and glycerol, have also been reported as secondary ligands to improve the size distribution of nanoprisms even though they are not essential to the formation of silver nanoprisms. Therefore, in this study, we synthesized TSNPRs according to the direct chemical reaction approach reported by Yin et al in which TSNPRs were stabilized by citrate in the absence or presence of secondary capping agents with carboxyl groups, such as ethanol and glycerol.…”
Section: In°uence Of Capping Agentsmentioning
confidence: 99%
“…Finally, biopolymeric templates such as cellulose nanocrystals (CNCs) and nanofibers (CNFs) can also be used as stabilizers in the synthesis of AgNPs and AgNPrisms, allowing the production of new hybrid nanomaterials. These studies [33][34][35][36] used modified CNC and CNF surface chemistry. In this context, 2,2,6,6-tetramethylpyperidine-1-oxyl (TEMPO)-oxidized CNFs appear to be an excellent substrate for the stabilization of AgNPs synthesized by NaBH 4 reduction since most of the surface primary C6 hydroxyls can be converted to carboxylates by TEMPO oxidation [37].…”
Section: Introductionmentioning
confidence: 99%